2000
DOI: 10.1046/j.1365-2141.2000.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine allows completion of chemotherapy in lymphoma patients with hepatitis B reactivation

Abstract: Reactivation of hepatitis B virus in patients receiving chemotherapy for non-Hodgkin's lymphoma (NHL) may give rise to hepatitis, hepatic failure and death, and prevent further chemotherapy. We report four patients with NHL in whom hepatitis flare-up was observed after two (three patients) and six (one patient) cycles of chemotherapy. After spontaneous recovery, they were treated with Lamivudine (100 mg/day), which enabled completion of chemotherapy without further hepatitis B reactivation. In one patient, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 9 publications
1
50
0
1
Order By: Relevance
“…Based on other reports, it has been shown that the continuation of lamivudine for 1-6 months after chemotherapy is equally effective in reducing viral reactivation. [17][18][19]25 Because the patients in the current study had different pathologic subtypes of lymphoma, and because patients in the lamivudine group had a relatively short follow-up, improvements in survival were not observed. However, prophylactic lamivudine treatments allowed more patients with lymphoma to receive adequate cytotoxic chemotherapy, and it would be reasonable to predict an increased survival advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on other reports, it has been shown that the continuation of lamivudine for 1-6 months after chemotherapy is equally effective in reducing viral reactivation. [17][18][19]25 Because the patients in the current study had different pathologic subtypes of lymphoma, and because patients in the lamivudine group had a relatively short follow-up, improvements in survival were not observed. However, prophylactic lamivudine treatments allowed more patients with lymphoma to receive adequate cytotoxic chemotherapy, and it would be reasonable to predict an increased survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…16 The use of prophylactic lamivudine in patients with lymphoma who were receiving chemotherapy recently was reported in several small, retrospective studies. [17][18][19][20] Lee et al 21 reported a retrospective case-control study that compared 20 HBsAgpositive patients who received prophylactic lamivudine during chemotherapy with a group of 11 matched controls. Their results indicated that 17 patients (85%) patients in the controls group and 1 patient (9%) patient in the prophylactic group had hepatitis due to reactivation of HBV.…”
Section: Discussionmentioning
confidence: 99%
“…The potential clinical consequences of hbv reactivation include liver damage from reactivation hepatitis, interruption of cancer treatment, and a mortality rate of up to 5% 7 . Prophylaxis with anti-hbv nucleoside/nucleotide analogs such as lamivudine reduces the incidence and severity of reactivation hepatitis in hbv carriers receiving chemotherapy [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to rituximab use, risk factors for HBV reactivation in oncology patients include male sex, use of anthracyclines, corticosteroid treatment, hepatitis B e antigen (HBeAg) seropositivity, and pre-existing abnormalities in liver function tests (Table 4) [12]. Hepatic flare can consequently lead to interruptions in delivering curative chemotherapy, lasting as long as 100 days [33]. Such delays in chemotherapy may result in a decreased disease-free and overall survival [15].…”
Section: Reactivation Of Hepatitis B Virusmentioning
confidence: 99%